The immunomodulatory effects of RNA-based biomaterials on bone regeneration. (May 2023) - Wang, Chen-yu; Qin, Zi-xuan; Wei, Yu; Hao, Jia-xin; Zhu, Yi-fei; Zhao, Fei; Jiao, Kai; Ehrlich, Hermann; Tay, Franklin R.; Niu, Li-na
Abstract: The use of RNA as therapeutic agents is a visionary idea in contemporary medicine. Some forms of RNA can modulate the immune response of the host to enhance tissue regeneration events such as osteogenesis. Herein, RNA molecules commercially available for immunomodulatory applications (imRNA) were used to prepare biomaterials for bone regeneration. The polyanionic imRNA stabilized calcium phosphate ionic clusters to produce imRNA-ACP that had the capacity to mineralize the intrafibrillar compartments of collagen fibrils. For the first time, it was shown that incorporating imRNA-ACP into collagen scaffolds resulted in rapid new bone formation in cranial defects of mice. Both in vivo and in vitro results demonstrated that macrophage polarization was highly-sensitive to the imRNA-ACP containing collagen scaffolds. Macrophages were polarized into the anti-inflammatory M2 phenotype that produced anti-inflammation cytokines and growth factors. The favorable osteoimmunological microenvironment created by the scaffolds prevented their immunorejection and facilitated osteogenesis. The potential of RNA in creating immunomodulatory biomaterials has been underestimated in the past. The overall aim of this study was to explore the potential application of imRNA-based biomaterials in bone tissue engineering, with the competitive edge of facile synthesis and excellent biocompatibility. Statement of Significance: In this work, commercially available RNA extracted from bovine spleens for immunomodulatory applications (imRNA) were used to stabilize amorphous calcium phosphate (ACP) and induce mineralization within collagen fibrils. Incorporation of imRNA-ACP into collagen scaffolds regenerated new bone in-situ . Because of its immunomodulatory effects, the imRNA-ACP that was incorporated into collagen scaffolds modulated the local immune environment of murine cranial defects by altering the macrophage phenotype through JAK2/STAT3 signaling pathway. The novelty of this work existed in the discovery of RNA's potential in creating immunomodulatory biomaterials. With the competitive edge of facile synthesis and excellent biocompatibility, the imRNA-based biomaterials are potentially useful for future bone tissue engineering applications. Graphical abstract: Image, graphical abstract